Vibration Management for Slope Stability with “Signature Hole Analysis” Method in Open Pit Blasting Activity - Muhammad Syafiq Isnaya; Muhammad Fadil Bellico; Dwi Agung Priyanggoro (PERHAPI, 2019)
One of the impact blasting activity is Ground Vibration which will affect the stability of the slope. Research and experiment conducted using Signature Hole Analysis (SHA) for monitoring wave propagation in each block-strip used to model and predict vibration which caused by the blasting activity. Signature Hole Analysis combined with Scaled Distance has succeeded in becoming the solution of ground vibration management.